2022
DOI: 10.1038/s41598-022-11681-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional divergence of the pigmentation gene melanocortin-1 receptor (MC1R) in six endemic Macaca species on Sulawesi Island

Abstract: Coat color is often highly variable within and between animal taxa. Among hundreds of pigmentation-related genes, melanocortin-1 receptor (MC1R) plays key roles in regulating the synthesis of the dark eumelanin and the red–yellow pheomelanin. The six species of macaques that inhabit Sulawesi Island diverged rapidly from their common ancestor, M. nemestrina. Unlike most macaques, Sulawesi macaques commonly have a dark coat color, with divergence in shade and color pattern. To clarify the genetic and evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…In rs6059655, ASIP was shown to have significantly decreased levels of expression with the risk phenotype. ASIP functions as an antagonist to MC1R through α-melanocyte-stimulating hormone to modulate melanin pigmentation ( Robbins et al., 1993 ; Yan et al., 2022 ), though an inverse expression quantitative trait loci association with MC1R was found to be nonsignificant. On the basis of 2008 case-control study, a haplotype near ASIP was found to confer an increased risk of cutaneous melanoma (OR = 1.27, 95% CI = 1.02–1.57) without adjustment for pigmentation characteristics, whereas MC1R did not ( Gudbjartsson et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…In rs6059655, ASIP was shown to have significantly decreased levels of expression with the risk phenotype. ASIP functions as an antagonist to MC1R through α-melanocyte-stimulating hormone to modulate melanin pigmentation ( Robbins et al., 1993 ; Yan et al., 2022 ), though an inverse expression quantitative trait loci association with MC1R was found to be nonsignificant. On the basis of 2008 case-control study, a haplotype near ASIP was found to confer an increased risk of cutaneous melanoma (OR = 1.27, 95% CI = 1.02–1.57) without adjustment for pigmentation characteristics, whereas MC1R did not ( Gudbjartsson et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%